Experimental studies on coal water slurries prepared from coal gasification wastewater. Issue 1 (23rd November 2017) - Li, Dedi; Liu, Jianzhong; Wang, Jinqian; Bai, Qingcheng; Cheng, Jun; Cen, Kefa
Abstract: Coal gasification wastewater (CGW) contains high concentrations of pollutants and varying chemical components and thus is difficult to treat. CGW slurry (CGWS), which is prepared by blending coal, CGW, and additives, is a new wastewater utilization technology that can be used to efficiently and conveniently treat CGW. This work mainly investigated the slurryability, rheology, stability, and combustion properties of CGWS prepared from Shenhua and Yima coals. Results showed that (a) the maximum solid loading of CGWS was slightly lower than that of ordinary coal–water slurry (CWS), but CGWS exhibited better pseudoplastic rheology and stability than CWS; moreover, increasing the solid loading of CGWS resulted in an increasingly pseudoplastic trend and enhanced stability; (b) CGW strengthened the combustion capacity of coke and CGWS demonstrating better ignition, burning, and burnout properties than CWS. These findings suggest that the use of CGWS technology in CGW treatment is beneficial economically and environmentally.